Family romance : John Singer Sargent and the Wertheimers - Strouse, Jean, 1945- (Farrar, Straus and Giroux, 2024)
"Jean Strouse captures the dramas, mysteries, intrigues, and tragedies surrounding John Singer Sargent's portraits of the Wertheimer family"--